Interleukin 1-Beta (IL-1β) Production by Innate Cells Following TLR Stimulation Correlates With TB Recurrence in ART-Treated HIV-Infected Patients. (1st February 2017) - Thobakgale, Christina; Naidoo, Kewreshini; McKinnon, Lyle R.; Werner, Lise; Samsunder, Natasha; Karim, Salim Abdool; Ndung'u, Thumbi; Altfeld, Marcus; Naidoo, Kogieleum
Abstract : Background: Tuberculosis (TB) remains a major cause of global morbidity and mortality, especially in the context of HIV coinfection because immunity is not completely restored following antiretroviral therapy (ART). The identification of immune correlates of risk for TB disease could help in the design of host-directed therapies and clinical management. This study aimed to identify innate immune correlates of TB recurrence in HIV+ ART-treated individuals with a history of previous successful TB treatment. Methods: Twelve participants with a recurrent episode of TB (cases) were matched for age, sex, time on ART, pre-ART CD4 count with 12 participants who did not develop recurrent TB in 60 months of follow-up (controls). Cryopreserved peripheral blood mononuclear cells from time-points before TB recurrence were stimulated with ligands for Toll-like receptors (TLR) including TLR-2, TLR-4, and TLR-7/8. Multicolor flow cytometry and intracellular cytokine staining were used to detect IL-1β, TNF-α, IL-12, and IP10 responses from monocytes and myeloid dendritic cells (mDCs). Results: Elevated production of IL-1β from monocytes following TLR-2, TLR-4, and TLR-7/8 stimulation was associated with reduced odds of TB recurrence. In contrast, production of IL-1β from both monocytes and mDCs following Bacillus Calmette–Guérin (BCG) stimulation was associated with increased odds of TB recurrence (risk of recurrence increased by 30% in monocytes and 42% in mDCs, respectively). Conclusion: Production of IL-1β by innate immune cells following TLR and BCG stimulations correlated with differential TB recurrence outcomes in ART-treated patients and highlights differences in host response to TB. Abstract : Supplemental Digital Content is Available in the Text.